2015
DOI: 10.1039/c4cc09527h
|View full text |Cite
|
Sign up to set email alerts
|

Target profiling of zerumbone using a novel cell-permeable clickable probe and quantitative chemical proteomics

Abstract: The first target profile for zerumbone in live cancer cells determined through quantitative competitive chemical proteomics with a cell-permeable probe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Optimising probe concentration and other labelling conditions can sometimes help, and quantifying enrichment in the presence and absence of a competitor (typically the parent NP) is one approach widely used to test whether a protein is a probe-specific hit. This approach was used to help identify the specific targets of the NPs zerumbone, 91 eupalmerin acetate, 89 hypothemicin 80 and fimbrolides, 85 for example. Multiple probes with modifications at different positions can be used to reduce the risk of probe-related off-targets and to ensure coverage of as many targets as possible (an approach used to identify possible targets of acivicin, for example).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimising probe concentration and other labelling conditions can sometimes help, and quantifying enrichment in the presence and absence of a competitor (typically the parent NP) is one approach widely used to test whether a protein is a probe-specific hit. This approach was used to help identify the specific targets of the NPs zerumbone, 91 eupalmerin acetate, 89 hypothemicin 80 and fimbrolides, 85 for example. Multiple probes with modifications at different positions can be used to reduce the risk of probe-related off-targets and to ensure coverage of as many targets as possible (an approach used to identify possible targets of acivicin, for example).…”
Section: Resultsmentioning
confidence: 99%
“…Spike-in SILAC was used by the Tate group to identify the targets of the NP zerumbone, for quantifying concentration-dependent competition of alkyne probe with the parent NP. 91 The cyclic sesquiterpene zerumbone, which has diverse anti-inflammatory activities, possess two electrophilic Michael acceptor systems with potential protein reactivity and so a probe 36 was synthesised with an alkyne attached at a distal site ( Table 2 ). A large batch of SILAC heavy cells were labelled with the probe, and subsequent triplicate samples in standard cell culture medium were prepared with probe and increasing concentrations of parent NP.…”
Section: Fishing For Targets: Probe-centric Approachesmentioning
confidence: 99%
“…While reports have been made regarding potential targets of curcumin, the approaches have generally been restricted in scope or otherwise limited in terms of their applicability to living cells 5 . Recently, clickable small molecule probes have been used in identifying the targets of many bio-active natural products or drugs 6 7 8 9 10 11 12 13 . In this study, we comprehensively identified in situ the specific and direct protein binding targets of curcumin in a colon cancer cell line (HCT116), via the synthesis of a cell-permeable clickable curcumin probe ( Cur-P ) combined with quantitative chemical proteomics methods ( Fig.…”
mentioning
confidence: 99%
“…Kalesh et al. demonstrates this method in their target identification study of zerumbone, a terpenoid compound derived from the Zingiber zerumbet plant with numerous possible therapeutic properties . Using a synthesized clickable cell‐permeable probe designated Yn‐Zer, HeLa cells were treated under normal conditions with a fixed Yn‐Zer concentration with increasing zerumbone concentrations, while an additional “heavy” labeled HeLa sample was treated with the same fixed concentration of Yn‐Zer.…”
Section: Quantitative Chemical Proteomicsmentioning
confidence: 99%